2003
DOI: 10.3390/i4030143
|View full text |Cite
|
Sign up to set email alerts
|

The Spin–Spin Coupling Constants in Ethane, Methanol and Methylamine: A Comparison of DFT, MCSCF and CCSD Results

Abstract: Abstract:The spin-spin coupling constants in ethane, methylamine, and methanol have been calculated using density-functional theory (DFT), coupled-cluster singlesand-doubles (CCSD) theory, and multiconfigurational self-consistent field (MCSCF) theory so as to benchmark the performance of DFT against high-level ab initio methods and experimental data. For each molecule, the Karplus curve has been evaluated at the three computational levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
22
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 35 publications
(61 reference statements)
4
22
0
Order By: Relevance
“…In some cases [57], B3LYP and MP2 gave very similar results but rather different from those obtained at the CCSD level or experimentally. In other cases [53][54][55][56], B3LYP provided satisfactory results compared with the MP2, QCISD and CCSD ones. Thus, because of the probable influence of the conformation on the vertical ionization potentials, it was decided to check the nature and number of "low" energy conformations as a function of the calculation level.…”
Section: Influence Of the Electronic Correlation Description Levelmentioning
confidence: 90%
See 1 more Smart Citation
“…In some cases [57], B3LYP and MP2 gave very similar results but rather different from those obtained at the CCSD level or experimentally. In other cases [53][54][55][56], B3LYP provided satisfactory results compared with the MP2, QCISD and CCSD ones. Thus, because of the probable influence of the conformation on the vertical ionization potentials, it was decided to check the nature and number of "low" energy conformations as a function of the calculation level.…”
Section: Influence Of the Electronic Correlation Description Levelmentioning
confidence: 90%
“…This was due to the fact that the electronic correlation is not the same for all the conformations as was also emphasized for dipeptides [49]. In the literature, the quality of B3LYP was often analyzed as compared with other correlated levels [50][51][52][53][54][55][56][57]. The B3LYP level was found unsuited to study transition metal complexes [50,51] or diradical species [52] but gave very satisfactory bond distances in metallocenes [55].…”
Section: Influence Of the Electronic Correlation Description Levelmentioning
confidence: 99%
“…b From Ref. [73]. c Experimental data known in the literature are from very old studies and are taken from Refs [7,73,74].…”
Section: Figurementioning
confidence: 99%
“…All the four contributions to spin-spin coupling 37 -41 (FC, spin dipolar, orbital diamagnetic, and orbital paramagnetic) were obtained using CP/DFT as implemented in the Gaussian03 suite of programs. 42 In a comparison of DFT, MCSCF, and CCSD results in ethane, methanol, and methylamine, Pecul and Helgaker 43 found that DFT methods perform well for the geminal coupling 2 J H,H 0 , but tend to overestimate vicinal H-H coupling constants. The basis set dependence of geminal H-H coupling in methane and substituted hydrocarbons has been extensively investigated.…”
Section: Scalar J-coupling Based On Cp/dft Methodsmentioning
confidence: 99%